The probability that a player wins the game by adding the numbers from the slips drawn from the box is 40%. If the rule changes and the player multiplies the numbers instead of adding them, the winning probability increases to 70%.
Explanation:
The game consists of drawing two numbers from the box and verifying whether their sum or product is even or odd. In Mathematics, for the sum to be even, both numbers must be odd or both must be even. If we check, we have 2 odd numbers (7, 9) and 3 even numbers (4, 6, 8). The combinations for even sum could be odd-odd or even-even. The total successful events would be 1 (odd-odd) + 3 (even-even) = 4 out of total 10 possible events (5C2), which gives us the probability of the player winning the game as 4/10 or 40%
Now, whether the probability changes when we multiply instead of adding: Yes, it does! In Mathematics, an even number results when multiplying any number by an even number, regardless of whether the other number is odd or even. Therefore, since 3 out of 5 numbers are even, the probability that the player wins if they multiply the two numbers they select instead of adding them is greater, confirmed by calculating combinations again and we find 7 out of 10 possible events yield an even product, therefore probability is 70%, which is greater than that of adding them.
Learn more about Probability in Mathematics here:https://brainly.com/question/32595744
#SPJ2
solve the following system of equations
2x – 3y = 6
4x+2y=4
Answer:
[tex]\boxed{(\frac{3}{2} ,-1)}[/tex]
Step-by-step explanation:
[tex]\left \{ {{2x-3y=6} \atop {4x+2y=4}} \right.[/tex]
It seems this system of equations would be solved easier using the elimination method (the x and y values are lined up).
Multiply everything in the first equation by -2 (we want the 4x to be able to cancel out with a -4x).
[tex]2x-3y=6 \rightarrow -4x+6y=-12[/tex]
Now line up the equations (they are already lined up - convenient) and add them from top to bottom.
[tex]\left \{ {{-4x+6y=-12} \atop {4x+2y=4}} \right.[/tex]
The -4x and 4x are opposites, so they cancel out.
Adding 6y and 2y gives you 8y, and adding -12 and 4 gives you -8.
[tex]8y=-8[/tex]
Divide both sides by 8.
[tex]y=-1[/tex]
Since you have the y-value you can substitute this in to the second (or first equation, it doesn't necessarily matter) equation.
[tex]4x +2(-1)=4[/tex]
Simplify.
[tex]4x -2=4[/tex]
Add 2 to both sides.
[tex]4x=6[/tex]
Divide both sides by 4.
[tex]x=\frac{6}{4} \rightarrow\frac{3}{2}[/tex]
The final answer is [tex]x=\frac{3}{2} ,~y=-1[/tex].
[tex](\frac{3}{2} ,-1)[/tex]
Which functions has the graph shown?
Answer:
C.
Step-by-step explanation:
Let's identify some points here that are on the graph:
(0,0), (pi/2,-1), (pi,0).
Let's see if this is enough.
We want to see which equation holds for these points.
Let's try A.
(0,0)?
y=cos(x-pi/2)
0=cos(0-pi/2)
0=cos(-pi/2)
0=0 is true so (0,0) is on A.
(pi/2,-1)?
y=cos(x-pi/2)
-1=cos(pi/2-pi/2)
-1=cos(0)
-1=1 is false so (pi/2,-1) is not on A.
The answer is not A.
Let's try B.
(0,0)?
y=cos(x)
0=cos(0)
0=1 is false so (0,0) is not on B.
The answer is not B.
Let's try C.
(0,0)?
y=sin(-x)
0=sin(-0)
0=sin(0)
0=0 is true so (0,0) is on C.
(pi/2,-1)?
y=sin(-x)
-1=sin(-pi/2)
-1=-1 is true so (pi/2,-1) is on C.
(pi,0)?
y=sin(-x)
0=sin(-pi)
0=0 is true so (pi,0) is on C.
So far C is winning!
Let's try D.
(0,0)?
y=-cos(x)
0=-cos(0)
0=-(1)
0=-1 is not true so (0,0) is not on D.
So D is wrong.
Okay if you do look at the curve it does appear to be a reflection of the sine function.
can someone help me pls?
Answer:
graph c
Step-by-step explanation:
there is no slope since it doesn't go up/down by anything or over by anything. meaning there is no increase or decrease.
How do you solve 0.3r = 2.1
I know the answer I just need to show my work
Answer:
7
Step-by-step explanation:
0.3r = 2.1
r = 2.1 ÷ 0.3
r = 7
identify the transformation taking place in this function. y = x^2 +8. a. translation down 8 units. b. translation left 8 units. c. translation right four units. d. translation up 8 units.
Answer:
D. if we are describing how to get from y=x^2 to y=x^2+8.
Step-by-step explanation:
If we are describing how to get from y=x^2 to y=x^2+8, then the transformation is just a translation of 8 units up.
If the equation was y=x^2-8, it would have been down 8 units.
If the equation was y=(x-8)^2, it would have been right 8 units.
If the equation was y=(x+8)^2, it would have been left 8 units.
if the translation T maps point A(-3,1) onto point A'(5,5), what is he translation T?
Answer:
< 8, 4 >
Step-by-step explanation:
Consider the coordinates
x- coordinate A - 3 → A' 5 → that is + 8
y- coordinate A 1 → A' 5 → that is + 4
Hence T = < 8, 4 >
or (x, y) → (x + 8, y + 4)
The translation T is given by:
T(x,y)=(x+8,y+4)
i.e. it shifts the point 8 units to the right and 4 units up.
Step-by-step explanation:The translation is the transformation that changes the location of points of the figure but there is no change in the shape as well as size of the original figure.
It is given that:
The translation T maps point A(-3,1) onto point A'(5,5).
so, if the translation rule that is used is:
(x,y) → (x+h,y+k)
Here
(-3,1) → (5,5)
i.e.
-3+h=5 and 1+k=5
i.e.
h=5+3 and k=5-1
i.e.
h=8 and k=4
Hence, the translation is 8 units to the right and 4 units up.
Today, Jana picked 15 flowers from her garden. This is 5 more than what she picked yesterday. How many flowers did Jana pick yesterday? F. 10. G. 20. H. 25. I. 30.
Answer:
F. 10
Step-by-step explanation:
She had 15 flowers today
So if she had 5 more than yesterday
You subtract the 5 to get how much she had yesterday
15-5=10
Answer:
F. 10
Step-by-step explanation:
Today: 15 flowers
: 5 more than yesterday
more than means add
15 = 5+ yesterday
Subtract 5 from each side
15-5 = 5+ yesterday -5
10 = yesterday
Trey is a car salesman who earned a base pay of $47,300 and was paid
commission of 15% for each car he sold. If x represents total sales in dollars,
then which of the following equations best represents Trey's total pay in
dollars?
Answer:
Trey earns a base pay of $47,300 plus 15% for each car sold.
The equation that represets Trey's total pay in dollars is:
y = $47,300 + 0.15x
Where $47,300 represents the base pay, and 0.15x represents the money he earn for the total cars sold.
Answer:
[tex]y=47,300+0.15x[/tex]
Step-by-step explanation:
Let x represent total sales in dollars.
We have been given that Trey earns base pay of $47,300 and was paid commission of 15% for each car he sold.
Since Trey is paid 15% for each car he sold and total sales were x dollars, this means his commission would be 15% of x that is [tex]\frac{15}{100}x=0.15x[/tex].
The total salary of Trey would be base salary plus commission: [tex]y=47,300+0.15x[/tex]
Therefore, the equation [tex]y=47,300+0.15x[/tex] represents Trey's total pay in dollars.
(07.03 MC)
Choose the correct simplification of the expression (3xy4)2(y2)3.
6x2y14
9x2y14
9x3y11
6x3y11
Answer:
9x²y¹⁴
Step-by-step explanation:
[tex]\tt (3xy^4)^2(y^2)^3\\\\=3^2x^2y^{4\cdot2}\cdot y^{2\cdot3}\\\\=9x^2y^{8}\cdot y^{6}\\\\= 9x^2y^{8+6}\\\\= 9x^2y^{14}[/tex]
The graph below shows a system of equations: Draw a line labeled y equals minus x plus 5 by joining the ordered pairs 0, 5 and 5, 0. Draw a line labeled y equals x minus 1 The x-coordinate of the solution to the system of equations is ___ . (5 points)
Answer:
The x-coordinate of the solution is x=3
Step-by-step explanation:
we have
[tex]y=-x+5[/tex] ------> equation A
[tex]y=x-1[/tex] ------> equation B
Solve the system of equations by substitution
Substitute equation B in equation A and solve for x
[tex]x-1=-x+5[/tex]
[tex]x+x=5+1[/tex]
[tex]2x=6[/tex]
[tex]x=3[/tex]
Find the value of y
[tex]y=x-1[/tex] ------> [tex]y=3-1=2[/tex]
The solution of the system of equations is the point (3,2)
therefore
The x-coordinate of the solution is x=3
Answer:
x = 3
Step-by-step explanation:
i did the same test and got it right
If sin A = 3/5 and the cosA =4/5 then what is tan A
Answer:
Tan A = 3/4
Step-by-step explanation:
sin A = y/r
Cos A = x/r
Tan A = y/x
Answer:
3/4
Step-by-step explanation:
sin A = 3/5
cosA =4/5
We know that tan A = sin A / cos A
= 3/5 / 4/5
= 3/5 * 5/4
= 3/4
How do I solve this problem? Thanks!
Answer:
92
Step-by-step explanation:
87 + 91 + 92 = 270
270 / 3 = 90
2 + (-2 + 23) – Ӏ 8 - 9 Ӏ =
Answer:
Step-by-step explanation:
2+(-2+23)-/8-9/=
2+ 21- /-1/=
2+21-1=
2+20=
22
Please mark as brianliest! Hope this helps!
Answer:
Solution of the expression is 22.
Step-by-step explanation:
The given expression is 2 + (-2 + 23) – Ӏ 8 - 9 Ӏ
We have to solve this expression
2 + (-2 + 23) - | 8-9 |
= 2 + (21) - |-1 |
= 2 + 21 - 1 [Since absolute value of (-x) is x or |-x | = x ]
= 23 - 1
= 22
Solution of the expression is 22.
A garden has an area of 240 ft. Its length is 8 ft more than its width. What are the dimensions of the
garden?
Answer:
w=12
l=20
Step-by-step explanation:
The area can be found using the following equation:
[tex]A=lw[/tex]
Given the information provided, we are also told the following:
[tex]l=w+8[/tex]
Therefore, we can plug in our length and our area:
[tex]240=w(w+8)\\240=w^2+8w\\\\w^2+8w-240=0[/tex]
We can solve by using the quadratic formula.
[tex]w=\frac{-8+\sqrt{8^2-4(1)(-240)} }{2(1)}=12 \\\\[/tex]
w=12, so w+8=20.
Two classes are planning to go on a field trip together. One clas with 18 students is being joined by 6 boys and 11 girls from another class, giving an overall ratio of boys to girls on the field trip of 2 to 3. Boys made up what proportion of the original class?
To find the proportion of boys in the original class, divide the number of boys by the total number of students in the class.
Explanation:To find the proportion of boys in the original class, we need to compare the number of boys in the original class to the total number of students in the original class.
The original class had 18 students, and it was joined by 6 boys from another class. This means there are now 18 + 6 = 24 boys on the field trip.
The overall ratio of boys to girls on the field trip is 2:3, which means for every 2 boys, there are 3 girls. If we have 24 boys, we can find the number of girls by dividing 24 by 2 and then multiplying by 3. This gives us (24/2) * 3 = 36 girls.
So, the original class had 24 boys and 36 girls. To find the proportion of boys in the original class, we divide the number of boys (24) by the total number of students (24 + 36 = 60). This gives us 24/60 = 0.4, or 40%.
I ONLY HAVE TILL TONIGHT PLZ SAVE ME I WILL MARK YOU THE BRAINLEST IF YOU ANSWER MY FULL QUESTION
Answer:
This graph is a not a Function because it doesn't pass the vertical line test. The opened and closed circles are not in relation to the y-value and the x-value. This function also doesn't corresponds to one another, which messes up the domain and range.
Step-by-step explanation:
Consider the equation (x^m)=(x^13)^5 x(x^-8)^-5
The value of m is
A. 15
B. 28
C. 35
D. 70
Answer:
m = 106Step-by-step explanation:
[tex]x^m=(x^{13})^5x(x^{-8})^{-5}\qquad\text{use}\ (a^n)^m=a^{nm}\\\\x^m=(x^{(13)(5)})x(x^{(-8)(-5)})\\\\x^m=(x^{65})x^1(x^{40})\qquad\text{use} \ a^na^m=a^{n+m}\\\\x^m=x^{65+1+40}\\\\x^m=x^{106}\Rightarrow m=106[/tex]
alpha and beta are the zeros of the polynomial x^2 -(k +6)x +2(2k -1). Find the value of k if alpha + beta = 1/2 alpha beta(ITS URGENT)
Answer:
[tex]k=\frac{-11}{2}[/tex].
Step-by-step explanation:
We are given [tex]\alpha[/tex] and [tex]\beta[/tex] are zeros of the polynomial [tex]x^2-(k+6)x+2(2k-1)[/tex].
We want to find the value of [tex]k[/tex] if [tex]\alpha+\beta=\frac{1}{2}[/tex].
Lets use veita's formula.
By that formula we have the following equations:
[tex]\alpha+\beta=\frac{-(-(k+6))}{1}[/tex] (-b/a where the quadratic is ax^2+bx+c)
[tex]\alpha \cdot \beta=\frac{2(2k-1)}{1}[/tex] (c/a)
Let's simplify those equations:
[tex]\alpha+\beta=k+6[/tex]
[tex]\alpha \cdot \beta=4k-2[/tex]
If [tex]\alpha+\beta=k+6[/tex] and [tex]\alpha+\beta=\frac{1}{2}[/tex], then [tex]k+6=\frac{1}{2}[/tex].
Let's solve this for k:
Subtract 6 on both sides:
[tex]k=\frac{1}{2}-6[/tex]
Find a common denominator:
[tex]k=\frac{1}{2}-\frac{12}{2}[/tex]
Simplify:
[tex]k=\frac{-11}{2}[/tex].
Audrey has .x pounds of red grapes and y pounds of
green grapes. She has less than 5 pounds of grapes in
Which are reasonable solutions for this situation?
Check all that apply.
(-1,2)
(1.3.5)
(2, 2)
(4.5, 0.5)
(5,0)
Answer: (1,3,5) & (2,2)
Step-by-step explanation:
Find the vertices and foci of the hyperbola with equation x^2/4 - y^2/60 = 1
Answer:
Vertices of hyperbola: (2,0) and (-2,0)
Foci of hyperbola: (8,0) and (-8,0)
Step-by-step explanation:
The given equation is:
[tex]\frac{x^2}{4}-\frac{y^2}{60}=1[/tex]
The standard form of equation of hyperbola is:
[tex]\frac{(x-h)^2}{a^2}-\frac{(y-k)^2}{b^2}=1[/tex]
Center of hyperbola is (h,k)
Comparing given equation with standard equation
h=0, k=0
so, Center of hyperbola is (0,0)
Vertices of Hyperbola
Vertices of hyperbola can be found as:
The first vertex can be found by adding h to a
a^2 - 4 => a=2, h=0 and k=0
So, first vertex is (h+a,k) = (2,0)
The second vertex can be found by subtracting a from h
so, second vertex is ( h-a,k) = (-2,0)
Foci of Hyperbola
Foci of hyperbola can be found as
The first focus of hyperbola can be found by adding c to h
Finding c (distance from center to focus):
[tex]c=\sqrt{a^2+b^2} \\c=\sqrt{(2)^2+(2\sqrt{15})^2}\\c=8[/tex]
So, c=8 , h=0 and k=0
The first focus is (h+c,k) = (8,0)
The second focus is (h-c,k) = (-8,0)
Which statements about the graph of the function Fx=-x2-4x+2 are true check all that apply
Step-by-step explanation:
Just graph it and see if the descriptions fit the graph
(see attached)
A. We can see from the graph that the possible x-values are -∞ ≤ x ≤ +∞ . Hence limiting to domain to x≤ -2 this is obviously not true.
B. We can see from the graph that the vertex is y = 6 and that the entirety of the graph is under this point, hence range y<6 is true
C. We can see that the vertex is located at x=-2. Every part of the graph to the left of this point has a positive slope, hence the function is increasing for negative infinity to this point x=-2 is true
D) We can see that for the interval -4<x<∞, the graph actually increases between -4<x<-2, and then decreases after that. Hence this statement is not true.
E. it is obvious that the y intercept is y=2 which is positive. Hence this is true.
The graph of F(x)=-x^2-4x+2 is a downward-opening parabola with its vertex serving as the local and global maximum. There are no asymptotes for this quadratic function. The shape of the graph is best understood by examining its behavior over a range of x-values and by sketching it with the vertex and axis of symmetry.
The graph of the function F(x) = -x^2 - 4x + 2 represents a parabola opening downward because the coefficient of x^2 is negative. To understand the nature of the graph, we evaluate its characteristics by identifying the vertex, the axis of symmetry, and whether it has local or global extrema. The vertex of this parabola can be found using the formula -b/2a, which gives us the x-coordinate, and by substituting that back into the function for the y-coordinate. The axis of symmetry will be a vertical line passing through the vertex's x-coordinate.
Since this is a quadratic function, it does not have asymptotes because it extends indefinitely in both the positive and negative directions of the y-axis. Instead, the parabola will have a maximum point at the vertex, which is a local and global maximum because the parabola opens downward. Moreover, we should evaluate the function for a range of x-values to understand its behavior for large negative x, small negative x, small positive x, and large positive x.
Sketching the graph of this function would involve plotting the vertex, drawing the axis of symmetry, and selecting a few points around the vertex to determine the shape of the parabola.
Someone help that is good in math
For this case we have:
[tex]x <2[/tex]Represents the solution of all strict minor numbers to 2.
[tex]x \geq2[/tex] Represents the solution of all numbers greater than or equal to 2.
The solution set, according to the figure, is given by the union of [tex]x <2[/tex] and [tex]x\geq2[/tex]. Thus, the complete solution is given by all the real numbers.
Answer:
Option D
Which of the following lists of ordered pairs is a function
Answer:
A
Step-by-step explanation:
A function can't have the same number more than once, so the answer is A since there are no repeating numbers.
Let y = safe load in pounds and x = length in feet of a horizontal beam. A constant of proportionality k exists such that Y=k/x If a beam can hold 2,000 pounds at 15 feet, what is the safe load if the length of the beam is 10 feet?
Answers: 300 pounds, 3,000 pounds, 20,000 pounds
Answer:
3000 pounds
Step-by-step explanation:
first sub in info to find k
2000=k/15 ; multiply both sides by 15 ; k=30000. if k is the constant, then to find the safe load (y) with the new beam (x), we input our new info into the equation.
y=30000/10 ; y=3000
Answer:
Safe load of the beam is 3000 pounds.
Step-by-step explanation:
If a horizontal beam of x feet length can hold y pounds safe load, the expression that represents the relation between load and length of the beam is
y = [tex]\frac{k}{x}[/tex]
If y = 2000 pounds and x = 15 feet
then 2000 = [tex]\frac{k}{15}[/tex]
k = 15×2000 = 30000
Now we will calculate the safe load when beam is 10 feet long.
From the formula,
y = [tex]\frac{30000}{10}=3000[/tex] pounds
Therefore, safe load of the beam is 3000 pounds.
Tina's favorite shade of teal is made with 7 ounces of blue paint for every 5 ounces of green paint. Tyler's favorite shade of teal is made with 5 ounces of blue paint for every 7 ounces of green paint.
How does Tina's favorite shade of teal compare to Tyler's shade of teal?
A. Tina's favorite shade is more blue than Tyler's
B. Tina's favorite shade is greener than Tyler's
C. The two colors are the same
Answer:
A. Tina's favorite shade is more blue than Tyler's
Answer: The correct option is
(A) Tina's favorite shade is more blue than Tyler's.
Step-by-step explanation: Given that Tina's favorite shade of teal is made with 7 ounces of blue paint for every 5 ounces of green paint.
Tyler's favorite shade of teal is made with 5 ounces of blue paint for every 7 ounces of green paint.
We are to find how Tina's favorite shade of teal compare to Tyler's shade of teal.
The fraction of blue paint in Tina's favorite shade of teal is given by
[tex]F_{ti}=\dfrac{7}{7+5}=\dfrac{7}{12}[/tex]
and the fraction of blue paint in Tyler's favorite shade of teal is given by
[tex]F_{ty}=\dfrac{5}{7+5}=\dfrac{5}{12}[/tex]
We get
[tex]F_{ti}-F_{ty}=\dfrac{7}{12}-\dfrac{5}{12}=\dfrac{2}{12}=\dfrac{1}{6}>0\\\\\\\Rightarrow F_{ti}>F_{ty}.[/tex]
That is, the fraction of blue paint in Tina's favorite shade is more than the fraction of blue paint in Tyler's favorite shade.
Thus, Tina's favorite shade is more blue than Tyler's.
(A) is the correct option.
Jade decided to rent movies for a movie marathon over the weekend. the function g(x) represents the amount of money spent in dollars where x is the number of movies. does a possible solution of 6.5,$ 17.50 make sense for this function. Explain your answer
A.yes the input is and output are both feasible
B. no the input is not feasible
C. no the output is not feasible
D. no neither the input nor output is feasible
kinda.
x = total of movies rented, INPUT
g(x) = total cost for all movies rented, OUTPUT.
the point of ( 6.5 , 17.50) means, that 6.5 movies were rented at a price of 17.50 total, that makes sense since 17.5 is more than 6.5 so the price is more than the quantity, however, whoever rents 6.5 movies? I mean, unless the movie store clerk gives you 6 movies and then cuts another with a chainsaw and gives you half of another.
so, the input is not too feasible, since no one rents 6.5 movies.
Answer:
B. No the input is not feasible
because you cannot rent 6,5 movies :p
Two points are drawn on each side of a square with an area of 81 square units dividing the side into 3 congruent parts. Quarter-circle arcs connect the points on adjacent sides to create the figure shown. What is the length of the boundary of the bolded figure? Express your answer as a decimal to the nearest tenth.
Answer:
The length of the bold figure ABCDEFGH is 30.8 units
Step-by-step explanation:
* To solve the problem look to the attached figure
- There is a square of area 81 units²
∵ The area of the square = L² , where L is the length of the side of
the square
∵ The area of the square = 81 units²
∴ L² = 81 ⇒ take √ for both sides
∴ L = 9 units
- Two points are drawn on each side of a square dividing it into 3
congruent parts
∵ 9 ÷ 3 = 3
∴ The length of each part is 3 units
- Quarter-circle arcs connect the points on adjacent sides to create
the attached figure
∵ The radius of each quarter circle is 3 units
∵ The length of each side joining the two quarter circle is 3 units
∵ The figure ABCDEFGH consists of 4 quarters circle and 4 lines
- The length of the 4 quarters circle = the length of one circle
∵ The length of the circle is 2πr
∴ The length of the 4 quarters circle = 2 π (3) = 6π units
∵ The length of each line = 3 units
∴ The length of the figure = 6π + 4 × 3 = 30.8 units
* The length of the bold figure ABCDEFGH is 30.8 units
Answer:
30.8
Step-by-step explanation:
If h(x) = (fog) (x) and h(x) = 4 square root x+7, find g(x) if f(x) = 4 square root x+ 1
Answer:
[tex]g(x)=x+6[/tex] is the answer
given
[tex]h(x)=4\sqrt{x+7}[/tex] and [tex]f(x)=4\sqrt{x+1}[/tex].
Step-by-step explanation:
[tex]h(x)=(f \circ g)(x)[/tex]
[tex]h(x)=f(g(x))[/tex]
Inputting the given function for h(x) into the above:
[tex]4\sqrt{x+7}=f(g(x))[/tex]
Now we are plugging in g(x) for x in the expression for f which is [tex]4\sqrt{x+1}[/tex] which gives us [tex]4\sqrt{g(x)+1}[/tex]:
[tex]4\sqrt{x+7}=4\sqrt{g(x)+1}[/tex]
We want to solve this for g(x).
If you don't like the looks of g(x) (if you think it is too daunting to look at), replace it with u and solve for u.
[tex]4\sqrt{x+7}=4\sqrt{u+1}[/tex]
Divide both sides by 4:
[tex]\sqrt{x+7}=\sqrt{u+1}[/tex]
Square both sides:
[tex]x+7=u+1[/tex]
Subtract 1 on both sides:
[tex]x+7-1=u[/tex]
Simplify left hand side:
[tex]x+6=u[/tex]
[tex]u=x+6[/tex]
Remember u was g(x) so you just found g(x) so congratulations.
[tex]g(x)=x+6[/tex].
Let's check it:
[tex](f \circ g)(x)[/tex]
[tex]f(g(x))[/tex]
[tex]f(x+6)[/tex] I replace g(x) with x+6 since g(x)=x+6.
[tex]4\sqrt{(x+6)+1}[/tex] I replace x in f with (x+6).
[tex]4\sqrt{x+6+1}[/tex]
[tex]4\sqrt{x+7}[/tex]
[tex]h(x)[/tex]
The check is done. We have that [tex](f \circ g)(x)=h(x)[/tex].
Find the area of the parallelogram whose three of the vertices are (1, -2), (2, 3) and (-3, 2) in order. Also find its fourth vertex .
do it
like this
i have done by coordinates of geometry
Answer:
Area = 24 square unit,
Fourth vertex = (-4, -3)
Step-by-step explanation:
Suppose we have a parallelogram ABCD,
Having vertex A(1, -2), B(2, 3), and C(-3, 2),
Let D(x,y) be the fourth vertex of the parallelogram,
∵ The diagonals of a parallelogram bisect each other,
Thus, the midpoint of AC = midpoint of BD
[tex](\frac{1-3}{2}, \frac{-2+2}{2})=(\frac{2+x}{2}, \frac{3+y}{2})[/tex]
[tex](\frac{-2}{2}, 0)=(\frac{2+x}{2}, \frac{3+y}{2})[/tex]
By comparing,
[tex]-2=2+x\implies x=-4[/tex]
[tex]3+y=0\implies y = -3[/tex]
Thus, the fourth vertex is (-4, -3),
Now, the area of the parallelogram ABCD = 2 × area of triangle ABC (Because both diagonals divide the parallelogram in two equal triangles)
Area of a triangle having vertex [tex](x_1, y_1)[/tex], [tex](x_2, y_2)[/tex] and [tex](x_3, y_3)[/tex] is,
[tex]A=\frac{1}{2}|x_1(y_2-y_3)+x_2(y_3-y_1)+x_3(y_1-y_2)|[/tex]
So, the area of triangle ABC
[tex]A=\frac{1}{2}|(1(3-2)+2(2+2)-3(-2-3)}|[/tex]
[tex]=\frac{1}{2}(1+8+15)[/tex]
[tex]=\frac{1}{2}\times 24[/tex]
[tex]=12\text{ square unit}[/tex]
Hence, the area of the parallelogram ABCD = 2 × 12 = 24 square unit.
if you can buy 1/4 pizza for 5 dollars, how much can you purchase for 8 dollars? write your answer as a fraction
Step-by-step explanation:
¼ pizza is to 5 dollars as x pizza is to 8 dollars.
¼ / 5 = x / 8
Cross multiply:
5x = 2
Divide:
x = ⅖
You can buy ⅖ of a pizza.